The Relationship between Knowledge and Practice in Clinical Breast Examination among Women in Baghdad, Iraq - Taqi Mohammed Jwad Taher; Shaymaa Abdul Lateef Alfadhul; Zainab Abbas Hassooni; Luma Hikmat Al-Bayati; Ban Atta Najman; Iman kadhim Ajlan; Baraa Abdulsalam Hraiga; Alyaa Razzaq Abed; Roaa M. H. Shoker; Thaer Hashim AbdulMuttaleb; Gasik Aqeele (مجلة الكوفة الطبية)
Aim: This study aims to determine both the level  of knowledge, attitude, and practice  in clinical breast examination in women and the relationship between knowledge and practice.Data collection was performed within a three-month period starting from February 2019 on.